Боспор та його сусіди у II ст. до н.е. - Молєв, Є.О. (Археологія, 1995)
У статті на підставі писемних джерел та результатів найновіших археологічних досліджень розглядається питання про зв’язки Боспору з сусідніми племенами у II ст. до н. е. Во II в. до н.э. Боспор должен был решать проблемы взаимоотношений со скифами на западе, с сарматами (прохоровцами) в устье Танаиса, меото-сиракскими племенами в Прикубанье, ахейцами, зихами, гениохами и керкетами на юго-восточных границах.
Данные письменных источников и результаты новейших археологических исследований показывают, что со своими западными соседями Боспор поддерживал союзные отношения, обеспечивавшие ему военную поддержку с их стороны. Захват сарматами (прохоровцами) Нижнего Дона привел к отделению Танаиса. В Азии подчинение сираками части меотских племен привело к созданию меото-сиракского союза, опора на который позволяла активно выступать против Боспора. В итоге этой борьбы последние Спартокиды потеряли почти все владения в этом районе. Мнение Ю. М. Десятчикова о наступлении сатархов на границы Боспора в Азии не подтверждается источниками. Борьба Боспора с племенами у своих юго-восточных границ велась с переменным успехом.
Разгром скифов Таврики войском Диофанта прекратил оказание военной поддержки Боспору с их стороны и стал основанием для передачи Перисадом V своей власти Митридату Евпатору. Следствием этой передачи стал государственный переворот, осуществленный скифами во главе с Савмаком. In the 2nd cent. В. C. Bosporus had to solve problems of its interrelations with the Scythians in the west, with the Sarmatians (Prokhorovtsy) in the mouth of the Tanais, with the Maeoto-Sirakian tribes in the Kuban river area, with the Acheians, Zichans, Henioches and Kerketians on the south-eastern frontiers.
Data from written sources and results of the newest archaeological studies have shown that Bosporus maintained allied relations with its western neighbours, which gave it a military support from their side. Annexation of the Lower Don reaches by the Sarmatians (Prokhorovtsy) caused falling away of the Tanais. In Asia the Sirakians subdued the part of Maeotian tribes, which led to formation of the Maeoto-Sirakian alliance. Backed by that alliance, the Maeotian tribes often acted against Bosporus. As a result of that struggle the last Spartokids have Lost almost all their lands in that region. The view advanced by Yu. M. Desyatchikov on the arrack of the Satarches on the Bosporus frontiers in Asia is not confirmed by sources. The struggle of Bosporus frontiers in Asia is not confirmed by sources. The struggle of Bosporus against the tribes on its south-eastern boundaries was a varying success.
The Taurican Scythians utterly defeated by Diophantus ceased to render military support to Bosporus, which made Perisad V to give its rule to Mithridates Eupatorus. As a result of that the Scythians headed by Saumak made a state upheaval.